ESG, Corporate Governance, and Firm Value in Emerging Markets - Lusy; Rafles Ginting; Yustinus Budi Hermanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Firm value remains a critical research focus as rising sustainability pressures and growing investor attention to ESG practices continue to shape market assessments of corporate performance. This study investigates the effect of environmental, social, and governance practices on firm value, with Corporate Governance, particularly audit committee size, as a mediating variable in Indonesian publicly listed companies from 2018 to 2023. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), the research examines the interplay between ESG, governance mechanisms, and value creation. The results reveal that ESG has a significant positive impact on Tobin’s Q, highlighting its role as a value-creation strategy. In contrast, audit committee size shows negative effect on firm value, emphasizing that effectiveness matters more than the number of members. Mediation analysis indicates that the audit committee weakens the relationship between ESG and firm value through a suppressor effect, suggesting that ineffective governance may reduce the credibility of ESG benefits. These findings are discussed within the frameworks of stakeholder theory, signaling theory, and the resource-based view, reinforcing that sustainable value creation requires ESG to be integrated with effective governance mechanisms.